Independent oil palm smallholders are not homogeneous groups - Andrianto, A.; Komarudin, H. (CIFOR-ICRAF, 2022)
Forest, palm oil plantations and other types of land cover account for 51.8%, 21.5% and 26.7% of Kotawaringin Barat district land, respectively. Palm oil plantations comprise those managed by companies (18.1%) and smallholders (3.4%). Typologies are based on sampled plantation areas of 2,902 ha taken from 7% of the district’s total smallholder plantation areas. This amounts to 42,770 ha. There are 349 surveyed plots (defined as a compact oil palm plantation area owned by a smallholder) involving 308 households.